Desire and denial in Byzantium : papers from the thirty-first spring symposium of Byzantine studies, University of Sussex, Brighton, March 1997 /: papers from the thirty-first spring symposium of Byzantine studies, University of Sussex, Brighton, March 1997. (2016) - Unknown
No abstract available